Pengaruh Kualitas Pelayanan Terhadap Kepuasan Pasien Puskesmas Arjasari - Novia Wulan Nur Romdon; Alda Ramadhika (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2024)
Health services, whether in health centers, hospitals, or other health service institutions, are a system consisting of various components that are interrelated, interdependent, and influence each other. Patient satisfaction is created from the quality of health services so that good and quality health services will have a positive impact on health services, namely the creation of a well-established loyalty that forms word of mouth promotion that benefits service providers. In 2017, residents complained about the services provided by the Arjasari Health Center. They said that the medical staff at the Arjasari Health Center were considered unfriendly when examining patients. The type of research used by the author is quantitative research. The method used is the survey method, the survey method is the process of taking samples from a population and using questionnaires as the main data collection tool. The results of the study showed that there was an influence of service quality on patient satisfaction at the Arjasari Health Center of 50.5%. This is proven by the results of the determination test, that the coefficient of determination (R Square) value of 0.505 or equal to 50.5%, indicates that the variable of Service Quality (X) affects Patient Satisfaction (X) by 50.5% and the remaining 49.5% is influenced by other variables not studied.